Effects of JL13, a pyridobenzoxazepine compound, in dopaminergic and glutamatergic models of antipsychotic activity. Issue 1 (February 2021) - Andrade, Yane C.P.; Ropke, Jivago; Viana, Thércia G.; Fanelli, Chiara; Minaldi, Elisa; Batista, Luara A.; Issy, Ana C.; Del Bel, Elaine A.; Rodrigues, Lívia C.M.; Liégeois, Jean-François; Moreira, Fabrício A.
Abstract : The pyridobenzoxazepine compound, 5-(4-methylpiperazin-1-yl)-8-chloro-pyrido[2, 3-b][1, 5]benzoxazepine (JL13), has been developed as a potential antipsychotic drug. We tested the hypothesis that JL13 is efficacious in both dopaminergic and glutamatergic animal models of schizophrenia. We investigated JL13 for its efficacy to prevent cocaine- and ketamine-induced hyperlocomotion and MK-801-induced deficits in prepulse inhibition (PPI) of the startle reflex. Male Swiss mice received injections of JL13 (0.1–10 mg/kg) and were tested in the open field for basal locomotion. In separate experiments, the animals received injections of JL13 (0.1–3 mg/kg) followed by cocaine (10 mg/kg), ketamine (60 mg/kg), or MK-801 (0.5 mg/kg) and were tested in the open field for hyperlocomotion. In addition, it was also tested if JL13 prevented MK-801-induced disruption of PPI. Only the highest dose of JL13 impaired spontaneous locomotion, suggesting its favorable profile regarding motor side effects. At doses that did not impair basal motor activity, JL13 prevented cocaine-, ketamine-, and MK-801-induced hyperlocomotion. Moreover, JL13 prevented MK-801-induced disruption of PPI. Extending previous findings, this study shows that JL13 exerts antipsychotic-like activity in both dopaminergic and glutamatergic models. This compound has a favorable pharmacological profile, similar to second-generation antipsychotics.